Pulmonary embolectomy: results and technique - Praderi, Raúl (Cirugía del Uruguay, 1971)
Trendelenburg's operation, was practised only in exceptional cases of massive pulmonary embolism, although it had been performed for the first time in 1924. With the advent of extracorporeal circulation, utilizing simple machines which could be used in the patients' beds, this operation was once more incorporated to the surgical weapons employed in urgency cases. Modern methods of clinical study make it possible to act on the basis of correct diagnosis. Contemporary surgeons, with a better knowledge of the disease and better equipment and instruments, may perform this operation with greater possibility of success than thirty years ago, even without the aid of extracorporeal circulation. Obviously the anatomical conception of this operation outstripped complementary facilities of its time.